Norway : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2003)
As will become apparent in the assessments, Norway's membership in the European Statistical System shapes Norwegian official statistics and statistical policy in a number of ways. Norway produces and disseminates a significant share of its data consistent with the legal requirements of the system. Norway's macroeconomic statistics are of generally high quality. They are adequate to conduct effective surveillance, although the mission (held in Oslo during November 11-26, 2002, by the IMF Statistics Department) identified some shortcomings that may detract from the accurate and timely analysis of economic and financial developments and the formulation of appropriate policy.